ICD/ITKE Research Pavilion 2014–15: Fibre Placement on a Pneumatic Body Based on a Water Spider Web. (September 2015) - Doerstelmann, Moritz; Knippers, Jan; Koslowski, Valentin; Menges, Achim; Prado, Marshall; Schieber, Gundula; Vasey, Lauren; Menges, Achim
<x xml:space="preserve">Abstract</x> Process‐based biomimetics focuses on the transfer of biological principles to architectural construction. To realise the ICD/ITKE Research Pavilion 2014 ‐15, presented here by Moritz Doerstelmann, Jan Knippers, Valentin Koslowski, Achim Menges, Marshall Prado, Gundula Schieber and Lauren Vasey of the Institute for Computational Design (ICD) and Institute of Building Structures and Structural Design (ITKE) research team at the University of Stuttgart, sensor‐driven robotic fabrication was combined with advanced design computation and simulation. This enabled the construction of an architectural fibre structure on a pneumatic mould, drawing on the complex design of the web of a water spider.